DISCRIMINATION INTEGRATED DEVELOPMENTAL SUPERVISION MODEL - Dambo, Neffisatu (fólio - Revista de Letras, 2018)
Counselor supervision is important for the development of future counselors and for client safety. Supervision is a process that provides monitoring, training, consultation, and feedback to help with counselors’ development, skill, and competencies. Therefore, the purpose of this manuscript is to present the Discrimination Integrated Developmental Supervision Model (DIDSM), which is an integration of Bernard’s (1997) Discrimination process model and Stoltenberg and Delworth’s (1987) Integrated Developmental Model. The author will also discuss how the following DIDSM tenets are essential to counselor supervision: (a) the supervisory relationship, (b) modeling, (c) feedback, and (d) the awareness of self and others.